Effectiveness of the use of mineral fertilizers and the Gumistim fertilizer in the cultivation of winter wheat in conditions of radioactive contamina-tion - Viktor F. Shapovalov, Galina P. Malyavko, Ludmila Р. Kharkevich, Evgeni V. Рrosyannikov ,German L. Yagovenko (International Journal of Advanced Science and Technology, 2020)
The article presents the results of studies evaluating the effectiveness of various fertilizer systems and the humic preparation Gumistim in the cultivation of winter wheat of the Moscow-39 variety under the conditions of radioactive soil contamination. It was found that the use of fertilizers allows to increase the yield of winter wheat grain by 0.65-1.44 t/ha, the use of humic preparation Gumistim - by 0.31-0.99 t/ha, the combined use of fertilizers and Gumistim by 1.21-2, 43 t/ha compared to the reference sample. The maximum yield (4.56 t / ha) was ensured by the use of the full mineral fertilizer N120P90K150 in combination with the biological preparation Gumistim. The use of fertilizer and Gumistim biological preparation, both separately and in combination, contributed to a significant increase in the physical and chemical parameters of winter wheat grain quality in comparison with the reference sample. The use of fertilizer leads to a decrease in the accumulation of 137Сs in winter wheat grain by 1.26-2.44 times, the use of Gumistim biological preparation by 1.00-1.36 times, the use of fertilizer and Gumistim by 1.61-3.12 times in comparison with the reference sample, which ensured the production of normatively clean products in technogenically contaminated territory.